Qualification of the assistance and the teaching of the Nursing Process as a method of carrying out the Systematization of Nursing Assistance (Research, Society and Development, 2020)
This study aims to explore a teaching strategy that contemplates the relationship between the Nursing Process and the Systematization of Nursing Care. A qualitative, descriptive and exploratory research was carried out, having as a field of study the University of Vale do Taquari. The participants were thirty-one students of these subjects, who were followed in a 20-hour class. The instruments for data collection were a case study, applied in four classroom hours and the excerpts from the researcher's field diary that accompanied the integral workload, which were analyzed and categorized with Bardin's Analysis of Content (2016). Based on the findings, it was verified that the participants showed the problem situations listed in the case study, demonstrating their critical knowledge on the subject. However, it was observed that some participants stopped to the punctual clinical problems that the case study carried, delimiting a smaller opening to the plan of care. It was observed that the "Related" and "Evidenced" in the realization of the Nursing Process, making it broad and holistic in view of the needs of the case. It was also noticed, evidences that correlate the accomplishment of the Nursing Assistance Systematization, through the Nursing Process, as a method of data collection. So, it is considered that the use of the case study strategy showed the relationship between the Nursing Process and the Nursing Assistance Systematization.